Development of an Internet of Things (IoT)-based Air Quality Monitoring System in the Environment - Lourensius Andrew Sutrisno; Budhi Kristianto (SISTEMASI, 2026)
This study developed an Internet of Things (IoT)-based air quality monitoring system to measure temperature, humidity, and carbon dioxide (CO₂) levels in real time. The study employed a prototyping method consisting of problem identification, requirements analysis, system design and development, testing, and result analysis. The system utilizes a NodeMCU V3 as the microcontroller, an MQ-135 sensor for gas detection, a DHT11 sensor for temperature and humidity measurement, and an OLED LCD for local display. Measurement data are transmitted and stored on the ThingSpeak platform and can be accessed through an Android application. Testing was conducted under three conditions: a normal environment, a closed room without ventilation, and a polluted condition with cigarette smoke exposure. The results show that the system is able to responsively detect changes in air quality, with CO₂ levels recorded at 76 ppm under normal conditions, 183 ppm in the closed room, and 729 ppm in the polluted condition. The system operates stably and provides real-time data visualization, making it suitable for low-cost implementation in household environments and small communities.